Struktur Biaya Produksi dan Pendapatan Usahatani Nilam dan Pengolahan Nilam di Desa Raraatean Kecamatan Tompaso Baru Kabupaten Minahasa Selatan - Manorek, Kresentia Gabigael Afni; Benu, Noortje Marsellanie; Loho , Agnes Estephina (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
Patchouli is a plant that produces essential oils with high economic value and is widely used in various industries, such as perfume, cosmetics, food, and pharmaceuticals. This plant is widely cultivated by the people of Raraatean Village, Tompaso Baru District, South Minahasa Regency. This study aims to analyze the production cost structure and income of patchouli farming and processing in Raraatean Village, Tompaso Baru District, South Minahasa Regency. This study was conducted over two months, from May to June 2025. Data collection was conducted through direct interviews with patchouli farmers. Data analysis used cost analysis based on processing and income structure, calculating total costs incurred by farmers, income received by farmers, and a R/C ratio analysis. At each stage of the patchouli farming business, variable costs dominated compared to fixed costs. The cultivation stage recorded the highest variable costs at Rp 8,998,355, followed by post-harvest at Rp 8,940,713, and preparation at Rp 8,940,713. The highest cost was Rp 8,014,285, with the lowest being the harvest cost of Rp 5,627,141. Fixed costs at all stages were relatively small, with the highest value at Rp 111,667 in the preparation stage and the lowest at Rp 12,500 in the harvest stage. The average production cost per farmer, with an average number of plants of 13,357, was Rp 31,560,560, with an average revenue of Rp 67,857,142 and a net income of Rp 36,296,226. The R/C ratio of 2.15 indicates that for every Rp 1 of costs incurred, revenue of Rp 2.15 is generated, making patchouli farming and processing a profitable and viable business.